Bilevel Positive Airway Pressure and Continuous Albuterol for Pediatric Asthma Exacerbations - Patrick T. Wilson; Melisa Tanverdi; John T. Brinton; Lilliam Ambroggio; Stanley J. Szefler (JAMA Network Open, 2026)
Importance A substantial knowledge gap remains in understanding the specific role bilevel positive airway pressure (BPAP) in the emergency department (ED) for acute pediatric asthma exacerbations. Objective To examine whether the early application of BPAP in the ED for acute pediatric asthma exacerbations reduces duration of critical care management time. Design, Setting, and Participants This double-blind randomized clinical trial enrolled children between 5 and 17 years of age presenting to a single-center, quaternary, referral pediatric ED with an acute asthma exacerbation, a pediatric respiratory assessment measure of at least 4 (moderate severity), and prescribed continuous albuterol therapy between June 1, 2023, and May 31, 2025. Intervention Participants were randomized to either the intervention arm (BPAP) or control arm (sham BPAP, which delivers minimal pressure) for 4 hours. Neither the health care practitioners nor participants were aware of study arm allocation. Main Outcome and Measures The primary outcome measure was duration of continuous albuterol therapy. A sequential design with a planned interim analysis for futility and superiority was used, and a t test compared mean duration of continuous β-agonist therapy under an intention-to-treat approach. Results Sixty-six study participants (median [IQR] age, 10.2 [6.8-13.2] years; 35 [53.0%] male; 1 [1.5%] American Indian or Alaskan, 1 [1.5%] Asian, 21 [31.8%] Black or African American, 21 [31.8%] White, and 22 [33.3%] other race) were included in the primary analysis, with a mean (SD) pediatric respiratory assessment measure of 5.2 (1.9), indicating moderate disease. At the 50% interim analysis, participants in the BPAP study arm received a mean (SD) of 8.3 (8.5) hours of continuous albuterol vs 8.7 (10.0) hours in the control group (mean difference, −0.5 hours; 95% CI, −5.0 to 4.1 hours; P = .84). The study was stopped due to meeting a priori bounds for futility at the 50% interim analysis. No deaths, invasive mechanical ventilation, air leak syndrome, or aspiration pneumonia were observed in either study arm. Conclusions and Relevance In this randomized clinical trial of early initiation of BPAP in the ED, no clinically significant decrease in the duration of continuous β-agonist therapy in pediatric patients presenting with moderate asthma exacerbations was observed. Additional open-label studies in a more severe asthma cohort are required to better inform clinical practice. Trial Registration ClinicalTrials.gov Identifier: NCT05848115